Sperm cryopreservation in adolescents with cancer. (May 2021) - Reschini, Marco; Somigliana, Edgardo; Meazza, Cristina; Podda, Marta; Guarneri, Cristina; Giacchetta, Daniela; Massimino, Maura; Restelli, Liliana; Filippi, Francesca; Terenziani, Monica
Abstract: Objective: To evaluate whether sperm banking is under-used in adolescents with cancer. Study design: We reviewed our 33 years long experience of semen cryopreservation and identified male subjects with cancer aged 14−21 years who banked their sperm. We hypothesized as a referring model a constant rate of referral in every age category (uniform distribution). In addition, we evaluated whether the distribution of the referrals per age varied according to historical periods and compared semen quality in the different age groups. Results: Overall, 317 subjects were selected. A sharp increase with age emerged (p < 0.001): the number of cases augmented from 4 at age 14 years to 79 at age 21 years. This significant increase persisted even when focussing only on subjects older than 16–18 years. An improvement of the distribution of cases per age group emerged when limiting the analysis to the last decade of activity; however, the increase remained significant (p < 0.001). Finally, we investigated whether semen quality differed according to age groups and failed to show marked differences, suggesting that sperm banking even at the youngest ages could be of potential benefit. Conclusions: This study confirmed that sperm banking is under-used in adolescents with cancers. Future studies should better clarify the determinants of this low referral and identify interventions that can improve the situation.